Improved Health System Performance through better Care Coordination - Hofmarcher, Maria M.. (OECD Health Working Papers, 2007)
This report attempts to assess whether -- and to what degree - better care coordination can improve health system performance in terms of quality and cost-efficiency. Coordination of care refers to policies that help create patient-centred care that is more coherent both within and across care settings and over time. Broadly speaking, it means making health-care systems more attentive to the needs of individual patients and ensuring they get the appropriate care for acute episodes as well as care aimed at stabilising their health over long periods in less costly environments. These issues are of particular interest to patients with chronic conditions and the elderly who may find it difficult to "navigate" fragmented health-care systems that are often found in OECD countries. Interest in coordination of care issues is increasing Growing interest in these issues has reflected a shift in the demands placed on health-care services. Chronic conditions have become progressively more important and are absorbing a growing share of health-care budgets. Since most of the chronically ill are elderly, this share can be expected to rise as populations age over coming decades. At the same time, many reports suggest that the quality of care that the chronically ill receive may need improvement. With these developments occurring in a context of tight public finance, some countries have been attempting to improve both the quality of care provided to the chronically ill and reduce cost pressures via changes to the architecture of health-care systems that encourage greater care coordination...